Using of â€œI Love You 3000â€ Song in Pandemic Era in Teaching English at Mining Department of Engineering Faculty - Hidayati, Hidayati; Hudri, Muhammad; Isnaini, Isnaini; Rahmaniah, Rima; humaira, humaira (Muhammadiyah University of Mataram, 2021)
Vocabulary is one of the English components or sub-skill that must be taught to the students. The vocabulary has the role to develop the four language skills, they are listening, reading, writing and speaking. Many vocabularies that the students have, is the easier for them to develop it, especially in the pandemic era because of COVID-19, the teacher have to use a media like an English song to enrich the students at Mining Department of Engineering Faculty vocabularies. In order that, the purpose of this study was to investigate the use of song as a media whether it is effective or not in teaching vocabulary. The total population of this study involved 92 students but the sample of by using the purposive technique sampling got 20 students in A class as a control and 20 students at B for experimental class. The instrument of this study used multiple choice tests which consist of 20 items. The data was collected by using pre-test and post-test, then followed by analyzing the data based on Arikuntoâ€™s theory using descriptive design. As well as the manual computation the result also showed that the score of the t-test was 4.741. The researcher compare that t-table at the degrees of freedom (df) (Nx + Ny)-2 . df = 20 + 20 â€“ 2 = 38. The degree of freedom of 38 is at the competenceÂ interval of 0.05 (95%) is 2.024 and 0.01 (99%) is 2.711. the comparison is done between t-test formulated with t-table in which results is 4.741Â it is to found that the t-table of â€œtâ€ indicated: t-test 4.741Â >Â t-table. It means that the mean score of the experimental class was higher than control class. So, the researcher concluded that the use of song â€œI Love You 3000â€ is effective in teaching learning English at Mining Department in academic year 2018/2019 and it means that the use of song as an alternative hypothesis (Ha) is accepted. (10 pt)